Guardianship over women in the marriage contract and its qaésprovisions - حفصة عزيزي (Tamanrasset University Center, 2021)
The marriage contract is one of the contracts that Islam meant about, sanctifying and preserving it for its privacy and importance, it is about symptoms, genealogies, and the survival of the human species. Whereas the effects of the marriage are not limited to the woman alone, but to her family and society, As a brother-in-law arises and has many rulings, Therefore, the majority of scholars stipulated the guardian to conclude the contract due to the multiple interests involved, However, he must ask her permission and consult her, He has no right to prevent her from marrying and harming her. There are conditions in the guardian and provisions relating to the arrangement of those who have the right to guardianship in the event of their presence and absence.